Efeito da sílica sol-gel na estrutura e resistência mecânica à compressão de pasta de cimento portland e de concreto de pós reativos - Michelle Cristina de Freitas Costa (2016)
The pozzolanic effect of the sol-gel silica additive on the structure andcompressive strength of Portland cement paste of high initial resistance and reactive powder concrete, with low factor water/cement, was analyzed. Two silicas of high specific surface area (S1 and S2), nanostructured, were synthesized by sol-gel process, characterized and used in cement paste and in reactive powder concrete, replacing the silica fume (SA). The hydration of the cement paste was studied by X-ray diffraction during the curing process. The compressive strength ofthe cement pastes and reactive powder concrete samples, with sol-gel silica and silica fume as pozzolanic additives, was evaluated. Density and porosity measurements by the Archimedes principle were also performed in order to discuss the structural variations in the samples. In the cement paste samples, the results showed that there were similar structural evolutions along the curing process when using similar water/cement factors. However, the sol-gel silicas of high specific surface area (S1 and S2) showed to have a significant pozzolanic power, and in the case of S1, higher than the commercial silica fume (SA). The cement paste samples produced with sol-gel silica S2 presented mechanicalproperties, of compressive strength, higher than the samples produced with the other silicas studied due to a better compaction of the particles of the material. On the other hand, the reactive powder concrete samples with sol-gel silica S2 showed mechanical properties, of compressive strength, only higher than samples with sol-gel silica S1 prevailing the best results of compressive strength for the samples with silica fume (SA). The sol-gel silicas produced seem to hinder the particles packaging of the reactive powder concrete, decreasing the mechanical properties. In general, sol-gel silica has been shown to be more efficient with respect to the mechanical properties of the cementitious material when this silicahas less micro and mesoporos, because less water is necessary during the molding step